Hemorrhagic pericardial effusion 6 months following atrial septal defect device closure: Has it eroded? - Alaina Zameer; Chetan Patel; Lamk Kadiyani; Damandeep Singh; Shivam Goel; Sivasubramanian Ramakrishnan (Annals of Pediatric Cardiology)
Transcatheter closure of atrial septal defect (ASD) is the preferred modality of treatment. Pericardial effusion occurring late after ASD device closure is extremely rare, and device-related erosion is the most likely possibility. We describe a 41-year-old male who underwent ASD device closure with a 32-mm Amplatzer Septal Occluder device and who developed cardiac tamponade 6 months after the procedure. Extensive investigations did not reveal any evidence of erosion. Given the endemicity of tuberculosis in India, exudative pericardial effusion, a positive tuberculin skin test, and the presence of a few matted mediastinal lymph nodes, the patient was started on antitubercular therapy. There was no reaccumulation of pericardial fluid at subsequent follow-ups. To conclude, not all hemorrhagic pericardial effusions following device closure of ASD are secondary to erosions. After ruling out device erosion, other etiologies for pericardial effusion should be carefully searched for.